India and the Pacific Alliance: opportunities and challenges - Baroni, Paola Andrea (2020)
Historically, India’s links with Latin America have been cordial, but they lacked of any substance. India approached the region after the political and economic reforms carried out in the 1990s. Even though the commercial dimension was where most efforts have concentrated, there has not been a substantial increase in values. The Latin American region has used regional integration processes as instruments for development and as means to link with other international actors, like India. The Pacific Alliance, with a vocation towards Asia, is an integration process of open regionalism, whose members are the main trading partners of India in the region. In this sense, it can play the role of a bridge between the Asian and Latin American regions and it can serve as a base for building interregional links. The objective of this work is to carry out an analysis of India´s links with the member countries of the Pacific Alliance. The focus is on the commercial and investment aspects, without putting aside the political one, and on the opportunities and challenges of those links.